Aortic valve assessment. Anatomical study of 100 healthy human hearts - Marcelo Biscegli Jatene; Rosangela Monteiro; Maria Helena Guimarães; Siomara Christina Veronezi; Márcia Kyiomi Koike; Fabio Biscegli Jatene; Adib Domingos Jatene (Arquivos Brasileiros de Cardiologia, 1999)
PURPOSE: To assess anatomical characteristics of the aortic valve, so that they may be useful in diagnostic situations and surgical treatment. METHODS: The study analyzed 100 healthy fixed human hearts; 84% of them obtained from males, 61% of them from Caucasian individuals. The ages of the individuals ranged from 9 to 86 years (mean 30±15.5 years). The characteristics assessed related to age, sex, and race were the following: number and height of the cusps, size of the lunulae, internal and external intercommissural distance, position of the coronary ostium in relation to the aortic valve, position of the ventricular septum in relation to the aortic valve, thickness of the cusps. RESULTS: All hearts assessed had a tricuspidal aortic valve. In regard to the height of the cusps and size of the lunula, the left coronary cusp was larger, followed by the right coronary cusp and the noncoronary cusp. The internal and external intercommissural distances had mean values of 24.6±5.7mm and 19.7±7mm, respectively. In regard to the position of the coronary ostia, in one heart two ostia emerged from the left coronary sinus, and in another, the ostium was supracommissural. The mean diameter of the aorta was 21.8±3.6mm, and there were no significant sexual or racial differences, but the diameter increased progressively with the increase in age. The thickness of the cusps did not show any significant difference in the 3 points assessed. CONCLUSION: The aortic valve annulus did not show a perfect circumference, with some variations in the measurements of the annulus, in the cusps and in the relation with the ventricular septum.